Complete plastome sequence of the Narcissus tazetta Var. chinensis: an important flower resource. Issue 3 (2nd July 2020) - Li, Yongfu; Li, Xuan; Zhang, Cheng; Zhu, Hong; Duan, Yifan; Chen, Shun; Chen, Wandong; Wang, Xianrong
Abstract: Narcissus tazetta var. chinensis is an important economic perennial herb in China. In this study, the complete plastid genome was assembled from the next-generation sequencing data. The circular genome is 159, 376 bp long, and comprises a pair of inverted repeat regions (28, 492 bp for each), a large single-copy region (85, 941 bp), and a small single-copy region (16, 451 bp). It encodes 133 genes, including 87 protein-coding genes, 38 tRNAs genes, and 8 rRNA genes. The GC content of N. tazetta var. chinensis cp genome is 38%. Phylogenetic analysis indicates that N. tazetta var. chinensis was closely relate to Narcissus porticus . The complete plastome genome will provide a useful genetic resource for the conservation and garden utilization in the future.